2006
DOI: 10.1086/508737
|View full text |Cite
|
Sign up to set email alerts
|

9.7 μm Silicate Features in Active Galactic Nuclei: New Insights into Unification Models

Abstract: We describe observations of 9.7 m silicate features in 97 AGNs, exhibiting a wide range of AGN types and of X-ray extinction toward the central nuclei. We find that the strength of the silicate feature correlates with the H i column density estimated from fitting the X-ray data, such that low H i columns correspond to silicate emission, while high columns correspond to silicate absorption. The behavior is generally consistent with unification models in which the large diversity in AGN properties is caused by v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
238
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(288 citation statements)
references
References 48 publications
48
238
2
Order By: Relevance
“…This result can be seen more clearly in Fig. 4, where we plot the 9.7 μm optical depth as a function of the X-ray column density for both the 12 μm sample as well as the sample of Shi et al (2006). We note that the latter is based mainly on the optically selected sample of Risaliti et al (1999).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…This result can be seen more clearly in Fig. 4, where we plot the 9.7 μm optical depth as a function of the X-ray column density for both the 12 μm sample as well as the sample of Shi et al (2006). We note that the latter is based mainly on the optically selected sample of Risaliti et al (1999).…”
Section: Discussionmentioning
confidence: 73%
“…We discuss this in detail in the following section. Shi et al (2006) described observations of 9.7 μm features in 97 AGN including a wide range of types. They found that the strength of the silicate feature correlates with the hydrogen column density, derived from X-ray observations in the sense that the low column densities correspond to silicate emission, while high columns correspond to silicate absorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If this unification scenario is correct, infrared observations of the nuclei of radio galaxies may act as calorimeters that indicate the levels of accretion activity. The dust tori, believed to be clumpy and to extend out to radii of tens to hundreds of parsecs (Krolik & Begelman 1988;Nenkova et al 2002;Granato et al 1997;Shi et al 2006), reradiate the optical and ultraviolet emission originating from the accretion disks surrounding the supermassive black holes (>10 6 M ). However, only radio galaxies displaying high-excitation narrow-line optical emission, referred to as high-excitation radio galaxies (HEGs), are understood to host obscured broad line and bright continuum emission, and to be in the process of active black hole accretion (Barthel 1994;Laing et al 1994).…”
Section: Introductionmentioning
confidence: 99%